(untitled) (Revista Brasileira Multidisciplinar, 2021)
Therapeutic residency is one of the strategies of psychiatric reform to change the logic of segregation. It receives people with chronic mental disorders, who may have their occupational performance compromised. The goal is to analyze the occupational performance of residents of therapeutic residences in a municipality in Minas Gerais; and assess how these residents perceive their own mental health after moving to the Residential Therapeutic Service. Method: This is an exploratory descriptive cross-sectional study, of quantitative / qualitative nature. 22 residents of therapeutic residences took part in the research. The data were collected in the residences on the services premises through an interview and the Canadian Occupational Performance Measure, being assessed through the analysis of categorical thematic content. Results: The three categories of the Canadian Occupational Performance Measure (self-care, productivity and leisure) were considered and two other additional categories were established: social participation and health perception. Conclusion: This study shows that there is a loss in the occupational performance of residents, whether due to years of illness or hospitalization, but that they highly value autonomy in the occupations they still perform; and that environmental aspects contribute positively to the perception of health of these people.